SOIL MICROORGANISMS ACTIVITY ON SEVERAL TYPES LAND USE IN THE VILLAGE OF PELEMPAI JAYA, SUBDISRTICT OF ELLA HILIR DISTRICT OF MELAWI - SARTOPO, SARTOPO SARTOPO (Jurnal Sains Pertanian Equator, 2017)
The aim of this research is to study soil mircoorganisms population and their activities (especially bacteria and fungi) on several types of land use namely rubber and palm oil plantation, mixed farming and upland rice field. The research was conducted on Juni 2016 until Agustus 2016. Soil samples were collected from Pelempai Jaya Village of Ella Hilir Subdistrict, District of Melawi. Soil analysis were conducted in the Biology and Soil Biotechnology Laboratory and Chemical and Soil Fertility Laboratory, Faculty of Agriculture, Tanjungpura University. The parameters observed were soil microorganims activity, soil microorganisms population, soil pH, C-organic, total N, C/N ratio, soil bulk density, soil texture and soil water content. The results showed that the types of land use caused a significant different in both activity and the number of soil microorganisms. Actvity and soil microorganisms population highest in rubber plantation (28,12 CO2/100 g/day and 5,062 x 106 CFU g-1). Activity and soil microorganisms population lowest in upland rice field (776 CO2/100 g/day 6 x 105 CFU g-1). Soil microorganisms population and their activities were influenced by the type of land uses. Keywords : Soil microorganisms activity and population